2020
DOI: 10.3390/ijms21051569
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Systemic IL-10 Levels Indicate Immunodepression Leading to Nosocomial Infections after Aneurysmal Subarachnoid Hemorrhage (SAH) in Patients

Abstract: Background: Aneurysmal subarachnoid hemorrhage (SAH) is a highly complex disease with very high mortality and morbidity. About one-third of SAH patients suffer from systemic infections, predominantly pneumonia, that can contribute to excess mortality after SAH. Immunodepression is probably the most important mechanism leading to infections. Interleukin-10 (IL-10) is a master regulator of immunodepression, but it is still not clear if systemic IL-10 levels contribute to immunodepression, occurrence of infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 42 publications
(68 reference statements)
3
25
0
Order By: Relevance
“…Intriguingly, on one hand the HMGB1 ligation of RAGE on monocytes/macrophages has been shown to enhance the ischemic brain damage, and on the other hand, HMGB1-signaling via RAGE drives an IL-10 release from M2-like macrophages (the anti-inflammatory phenotype of macrophages). In line with this notion, serum HMGB1 levels measured within 24 h after the aSAH showed a correlation with a latter increase in serum IL-10 levels measured on day 7 after the aSAH [21]. It is well known that anti-inflammatory mechanisms also upregulate in parallel to pro-inflammatory mechanisms to limit the damage, however, it would be interesting to evaluate further how these pro-inflammatory mechanisms are dominated by anti-inflammatory mechanisms, and how they contribute towards different post-aSAH complications and clinical outcomes, as several lines of evidence also report immunodepression after aSAH [21,54].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Intriguingly, on one hand the HMGB1 ligation of RAGE on monocytes/macrophages has been shown to enhance the ischemic brain damage, and on the other hand, HMGB1-signaling via RAGE drives an IL-10 release from M2-like macrophages (the anti-inflammatory phenotype of macrophages). In line with this notion, serum HMGB1 levels measured within 24 h after the aSAH showed a correlation with a latter increase in serum IL-10 levels measured on day 7 after the aSAH [21]. It is well known that anti-inflammatory mechanisms also upregulate in parallel to pro-inflammatory mechanisms to limit the damage, however, it would be interesting to evaluate further how these pro-inflammatory mechanisms are dominated by anti-inflammatory mechanisms, and how they contribute towards different post-aSAH complications and clinical outcomes, as several lines of evidence also report immunodepression after aSAH [21,54].…”
Section: Discussionsupporting
confidence: 75%
“…The elevated levels of HMGB1 were correlated with blood leukocytes and increased IL-6 levels [20]. Interestingly, HMGB1 levels measured on day 1 after the aSAH were also shown to correlate with elevated IL-10 levels later on day 7 after the aSAH [21]. Another clinical study described elevated CSF HMGB1 levels in acute hydrocephalus after the aSAH and strong correlations with different scores of aSAH severity, including Hunt and Hess grades, the World Federation of Neurological Surgeons (WFNS) score, and the Glasgow Coma Scale (GCS).…”
Section: Hmgb1 Is Released In Cerebrospinal Fluid (Csf) and Systemic mentioning
confidence: 85%
“…SAH patients, who developed any kind of infection, CVS or chronic hydrocephalus, had significantly higher serum IL-10 levels compared to controls. In addition, discharged SAH patients with poor clinical outcome (modified ranking scale 3–6 or Glasgow outcome scale 1–3) revealed significantly higher serum IL-10 levels [ 64 ]. Another promising predictive biomarker correlating with clinical neurological outcome might be chemokine C-C motif ligand 5 (CCL5).…”
Section: Role Of Neuroinflammation In Asahmentioning
confidence: 99%
“…Wessell et al showed that persistent systemic inflammation following aneurysmal subarachnoid hemorrhage was associated with SDHC and predicted its occurrence [82]. Chaudhry et al first reported a significant increase in serum IL-10 levels in SAH patients with chronic hydrocephalus on Day 7 [83]. IL-10 is an essential antiinflammatory cytokine secreted by almost all immune cells [84].…”
Section: Chronic Hydrocephalusmentioning
confidence: 99%